Pharmacy Education Crosses the Rubicon - Romanelli, Frank (Am J Pharm Educ, 2020)
The pandemic caused by the novel coronavirus identified in 2019 (COVID-19) has resulted in seismic changes throughout society. Accordingly, academia has been forced to adapt. Changes across all aspects of teaching and instruction have occurred. Students have departed campuses and prospects of their return remain unclear. The Academy, which is generally reluctant to change, has been forced to make rapid adjustments. Among other issues, pharmacy schools and colleges have been forced to mitigate changes to experiential education. Tremendous resources and energy have been invested to actuate the changes that have occurred. In many ways, the disruptions forced upon pharmacy education may usher in a new normal. The likelihood for even a partial return to the customary way of doing things appears increasingly unlikely.